Evaluación de la capacidad de sellado de cementos biocerámicos en la obturación de conductos radiculares. Revisión sistemática de estudios in vitro - Neciosup Farje, Johana Isabel (2020)
Objective: To systematically evaluate in vitro studies available in the literature that describe the sealing ability of bioceramic cements in the filling of root canals. Materials and Methods: An electronic search was conducted in the databases Pubmed, Embase, Scopus, Lilacs, Science Direct. In addition, the journals with the greatest impact factor in endodontics and available gray literature were accessed manually. Publications between January 1, 2009 and October 23, 2019 were considered. In vitro studies were included that used micro computed tomography (micro CT) as a means of evaluating unsealed voids, in addition to those comparing bioceramics with others conventional sealers. The process of selection, obtaining information and risk of bias analysis was performed in pairs reaching efficient levels of agreement. Results: Of a total of 319 articles, 6 were included for qualitative analysis. Comparative results showed values in favor of bioceramics. The percentages of unsealed voids range from 0.0015% to 9.67% of the total duct. At the apical level, these spaces are from 0.37% to 1,755%. At the same root level the volume of voids presented is from 0.301 to 0.324 mm3. At the risk of bias assessment, the studies accomplish the modified CONSORT items with a mean of 63.33%. Conclusion: Bioceramics based sealers showed good sealing ability in the apical third, with a moderate level of risk.